Autour de l'extrême littéraire - Hemmens, Alastair; Williams, Russell (Cambridge Scholars Publishing, 2012)
The extreme is an essential aspect of contemporary experience. Thrill-seekers spend the weekend in the search of the adrenaline rush of ""extreme sports"". In the political arena, the world has begun to rediscover the split between the ""extreme"" left and th